Detection of prostate cancer in the PSA gray zone using prostate-specific antigen mass ratio combined with PI-RADS score - Weilin Li; Zhiqi Wang; Weihong Zhao; Gaobo Zhou; Miaomiao Peng; Zhicheng Su; Tao-Hsin Tung (Journal of Men's Health, 2025)
Background: The study aimed to assess the diagnostic performance of prostate-specific antigen mass ratio (PSAMR) in combination with the Prostate Imaging Reporting and Data System (PI-RADS) score for detecting prostate cancer (PCa) in patients presenting with mildly elevated prostate-specific antigen (PSA) levels (4–10 ng/mL). Methods: A retrospective analysis was conducted involving 208 patients with PSA levels between 4 and 10 ng/mL who underwent multiparametric magnetic resonance imaging (mpMRI) and transrectal ultrasound-guided transperineal prostate biopsy. PSA-derived parameters and PI-RADS scores were incorporated into logistic regression models to predict the presence of PCa. Diagnostic accuracy was assessed using receiver operating characteristic (ROC) curve analysis. Additionally, Spearman’s correlation analysis was performed to determine the relationship between each parameter and the prediction model with disease severity ratings. Results: Of the 208 patients, PCa was confirmed by biopsy in 62 cases. The combination of PSAMR and PI-RADS score yielded an area under the ROC curve (AUC) of 0.874 (95% confidence interval (CI): 0.821–0.916, p < 0.001), which was higher than the AUCs for PSAMR or PI-RADS score alone, indicating superior diagnostic accuracy. Correlation analysis also revealed that the combined model had the strongest association with disease severity. The order of correlation coefficients was as follows: PSAMR combined with PI-RADS score (Model A) > Prostate-specific antigen density (PSAD) combined with PI-RADS score (Model B) > PI-RADS score alone > PSAMR alone > PSAD alone. Conclusions: The combination of PSAMR and PI-RADS score significantly enhances the accuracy of PCa detection in patients with PSA levels of 4–10 ng/mL. This approach may contribute to more effective screening strategies while minimizing unnecessary biopsies. Furthermore, given their positive correlation with disease severity, PSAMR and PI-RADS scores together may also assist in predicting PCa progression risk.